Phosphorus metabolism of the food system in the Guangdong-Hong Kong-Macao Greater Bay Area urban agglomeration - Lu, Yang; Huang, Wei; Cui, Shenghui; Deng, Jiexin; Zhang, Yin; Huang, Yunfeng; Gao, Bing (Frontiers in Sustainable Food Systems, 2025)
IntroductionPhosphorus (P) is a vital nutrient for food production, yet a significant pollutant when mismanaged.MethodsThis study analyzes the phosphorus flow of the food system in the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) in 2020, using a Substance Flow Analysis framework. The research examines natural and anthropogenic inputs, outputs and accumulation of phosphorus.ResultsResults reveal that the GBA is heavily dependent on external phosphorus inputs, with a total input of 187.69 Gg. The two largest sources of phosphorus inputs are aquaculture (36%) and food consumption (33%). The phosphorus use efficiency (PUE) in crop production, animal husbandry, and aquaculture were approximately 48.8, 32.37, and 10.01%, respectively. However, only 7.89% of phosphorus is recycled, while substantial losses (76% to soil and 24% to water bodies) exacerbate environmental pressures. Spatial analysis highlights distinct patterns between production-oriented cities (e.g., Jiangmen and Zhaoqing) and consumption-oriented cities (e.g., Shenzhen and Hong Kong).DiscussionPolicy recommendations include enhancing aquaculture management, improving phosphorus recycling technologies, and fostering intercity collaboration to create a sustainable phosphorus management framework. These findings provide critical insights for addressing phosphorus-related challenges in urban agglomerations.